ISOLATE TWO SPECIES OF COMPOSITAE FAMILY E.armatus BOISS&HAUSSKN AND E.cephalotes DC. BY MORPHOLOGICAL AND VEGETATIVE SHOOT APEX FOR THE FIRST TIME IN IRAQ - & et al., Al-Musawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Present study delts with morphological and vegetative shoot apex characteristics of two species  Echinops armatus and E.cephalotes (compositae) which collected during trips field to the northern areas of Iraq in the seasons of growth 2012-2014. As it presents the results and characters  had been shown for the first time in Iraq. plant species are perennial herbs spinous with woody, strong and solid stems that covered with many types of indumentums like spines and hairs, the study included characters of stems, leaves, involucres bracts and inflorescences as well as characters of growing points of the two species, and by examining buds in inflorescences found that the flowers are hermaphrodite, not sterile which containing all the reproductive organs like stamens, pollen grains, pistils and ovaries, an early dehesence as mature anthers and bloom before the maturation of pistils and disperse their pollen.The study also discussed variations within the characters and it became clear that the characters of leaves, stems and involucres especially inner cycle, including the importance of taxonomic great isolate the two species. Ranged prepare involucres braces  in the first species is (20-23) bracts while the number varied between (19-20) bracts in the other one. The study showed the importance of growing points  in isolating the two species where characterized by two meristematic area in longitudinal embryos species. The first spices recognized by two rows of cells, while the other one marked three rows or layers of components of Tunica cells area, and ensures find accurate measurements of parts phenotypic as well as illustrations of morphological and anatomical parts studied.